PERAN PEMUDA SEBAGAI PENERUS TRADISI SAMBATAN DALAM RANGKA PEMBENTUKAN KARAKTER GOTONG ROYONG - Nur Bintari, Pramudyasari; Darmawan, Cecep (Universitas Pendidikan Indonesia, 2016)
Currently youth behavior that is inconsistent with the character of the nation and the declining youth awareness of the splice. This study aims to obtain a picture of the implementation of mutual cooperation, shape, splice conservation efforts, associated with the formation of the youth character and know the community efforts to increase the appreciation of youth. The study used a qualitative approach, descriptive methods. Subjects were young, village, and community leaders. Data collection technique used observation, interview, and documentation study. Data were analyzed using data reduction, and conclusion. Results of the research is the role of youth as the next generation of tradition, study and understand the traditions, accompany the next generation in the process of understanding, implementation, and evaluation. The role of youth in the splice should be improved as a form of community service. Splice form is